Assessment of pressure sensitivity in the head region for Chinese adults. (November 2021) - Shah, Parth; Luximon, Yan
Abstract: Measurement of pressure threshold has found its applications in the fields of medical sciences and product design. Hence it has been a profound area of research interest for several decades. However, hardly any detailed investigation has been undertaken to measure the pressure threshold in the head region. In this study, Pressure Discomfort Threshold (PDT) and Pressure Pain Threshold (PPT) were measured for two hundred eighteen healthy Chinese adults at seventy-six anatomical locations, and further statistical analyses were performed on the acquired data to understand the relationship between different demographic parameters. The results suggest that the pressure sensitivity is low in the vertex region, moderate in the forehead and temporal area, and high in the facial and nasal region. From this study, pressure sensitivity maps were developed for PDT and PPT for Chinese adults. The measured pressure threshold data showed no significant relationship with age and Body Mass Index (BMI). Highlights: Pressure thresholds were measured for discomfort & pain at different regions of head. The measured values for PDT and PPT showed gender-based differences. PDT and PPT did not have significant relationship with age and BMI.